The Challenge of Coexistence: Changes in Activity Budget and Ranging Behaviour of Brown Howler Monkeys in Response to the Presence of Conspecifics and Heterospecifics - Sobral, Gisela; Fuzessy, Lisieux F. [UNESP]; de Oliveira, Claudio Alvarenga (Springer Nature, 2023)
The presence of other animals, both conspecifics and heterospecifics, is a major driving force for how animals organize themselves in space and time. Although theoretical models are available to explain the role of each in animal movement, fine-scale assessments of daily movement are scarce, particularly for primates. Hence, our goal was to assess whether and how the presence of conspecifics and heterospecifics influence spatiotemporal landscape use in two, wild, howler monkey (Alouatta guariba) groups. We followed the groups for 14 months in a large, continuous forest, during which we recorded their daily path length (DPL), home range, activity budget, feeding, and the presence of other groups (conspecifics) and other species (heterospecifics). The two groups differed in DPL, home range, proportion of fruits ingested, and time devoted to moving and resting. Partial least squares path modelling showed that variation in DPL was explained by the percentage of leaves or fruits ingested and by the presence of conspecifics, but not of heterospecifics. Group differences in several ecological variables emphasise the need to conduct further studies of space use with more groups in the same area to understand the underlying mechanisms of these differences. Moreover, our analysis shows that within-species interactions may be a stronger force in spatiotemporal organisation than interspecies interactions, at least in this folivorous primate. This is relevant from both a theoretical standpoint, and also when considering the consequences of habitat fragmentation and reduction. Deforestation leads to decreased resource availability and increased likelihood of encounters with conspecifics, which ultimately alters the proportion of food items ingested and increases the DPL, disrupting energy balance.
Keywords: Activity budget; Daily path length; Home range; Interspecific interactions; Intraspecific interactions; Time budget